Functional diversity of algal communities from headwater grassland streams: How does it change following afforestation? - Cibils Martina, Luciana (2015)
Pine afforestation of grassland streamsmay lead to changes in species traits and thereforefunctional diversity of epilithic algal community.Here, we studied trait-based responses in three grasslandand three afforested streams in a mountainwatershed of Co´rdoba, Argentina. We hypothesizedthat afforestation would reduce functional diversitythrough a simplification of periphyton architectureresulting from reduction in light availability, and thatchanges in hydrological periods would influencecommunity responses. Algal samples were collectedat each stream during two different hydrologicalperiods (high flow and low flow), and physicochemicalvariables were recorded. Selected traits includedstrategies and morphological characters related toresource access and disturbance resistance (size,morphological guild, resource requirement, attachmentmechanism and life-form). We calculated twoindices of functional diversity: Rao?s quadraticentropy (FDQ) and functional variance. Most traitcategories showed a significant effect of one or bothfactors; 26 % discriminated between vegetation types,26 % reflect the changes between hydrological periods,and 47 % were sensitive to both of them. Ourresults revealed some categories of traits that can beused to distinguish changes in riparian vegetation,such as unicellular life-form and high-profile guild.Functional diversity of single traits was affecteddifferently by pine afforestation. However, the mostintegrative index, the FDQ mean, partially supportedour hypotheses. Afforestation reduced FDQ mean by50 %, but only during low-flow period. FDQ mean washigh and similar between streams at high flow, whenenvironmental factors, such as discharge and temperature,could prevail on differences in riparianvegetation.